Diuretics - Mazzei, F.; Botre, F.; Di Paolo, F.; Pelliccia, A. (2003)
Diuretics are drugs that increase the amount of urine produced and excreted by the body. Their use determines a loss of salts and water from the body trough the urinary tract and the kidney. The reduction in circulatory volume and venous congestion relieve breathlessness and reduce peripheral oedema. Diuretics are mainly used in the treatment of hypertension, in acute and chronic heart failure and in the case of problems in fluid retention. Diuretics have been used for many years, thus their mode of action as well as adverse effects have been investigated and almost completely understood. To better understand the mode of actions and the effects of these drugs, we have to take into account all the nephron functionality, in order to observe the presence of compensatory mechanisms that are always upcoming whenever electrolyte homeostasis is perturbed. Diuretics are generally classified according to their site and mechanism of action in the renal tubule.